UV-responsive nano-sponge for oil absorption and desorption - Kim, Do Hyun; Jung, Min Chan; Cho, So-Hye; Kim, Sang Hoon; Kim, Ho-Young; Lee, Heon Ju; Oh, Kyu Hwan; Moon, Myoung-Woon (NATURE PUBLISHING GROUP, 2015)
Controlled surface wettability for oil has been intensively studied to remove industrial oil waste or oil spill pollution from seas or rivers. In particular, external stimuli-induced special wetting materials, such as photo-responsive TiO2, have attracted considerable attention for oil-water separation. In this study, a novel method is reported to fabricate a nano-sponge which is composed of hydrophobic hydrocarbon and hydrophilic TiO2 nanoparticles for oil absorption or desorption that are responsive to UV irradiation. The hydrocarbon in the nano-sponge could selectively absorb oil from water, whereas the absorbed oil is released into the water by TiO2 in response to UV irradiation. The nano-sponge functionalized porous polydimethylsiloxane released more than 98% of the absorbed crude oil with UV irradiation and air-bubbling. It could be continuously reused while maintaining a high absorption capacity and desorption efficiency without incurring secondary air or water pollution. This smart oil absorption/desorption methodology with excellent selectivity and recyclability with almost perfect removal of absorbed oil can be applied for oil-water separation, oil spill cleanup and reuse of spilled oil.
Keywords: WATER; SURFACES; SUPERHYDROPHOBICITY; WETTABILITY; SUPERHYDROPHILICITY; SUPEROLEOPHOBICITY; TRANSITION; MEMBRANES; TENSION; MESH